Fresno County Women Lawyers Annual Dinner: Honoring Mary Louise Frampton - Watkins, Howard::::::::: (1989)
Fresno County Women Lawyers President Ruth Ratzlaff announcing the 1st Annual Fresno County Women Lawyers Justice Pauline Davis Hanson Award to be presented by Justice Hanson herself and calls Justice Hanson to the microphone